Exploration of indigenous Trichoderma species for their use as biofertilizers, optimization of growth conditions and cultivation on cheap substrates - Dhurva Prasad Gauchan; Ashok Kumar Bhattarai; Shishir Pandey; Sunil Bhandari (Novel Research in Microbiology Journal)
Members of the genus Trichoderma have substantially improved the agricultural economy through inhibiting the phytopathogens, assimilating nutrients and inducing defensive metabolism against the environmental stresses. The major aim of this study was to isolate indigenous Trichoderma that can be used as a potential biocontrol agent (BCA). Currently, we isolated 14 native fungal isolates from vermicompost, agricultural soils and infected substrates, and identified them as Trichoderma spp. based on their morphological characteristics. Isolates designated V1D, V1F, V3D, V3F, W1, W2, KAL, NAR, BIOC, AG, RD and NIM resembled to T. viride, while MUSH and RF resembled T. harzianum. The ability of these isolates to assimilate different forms of sugars, nitrogen source (N) and phosphates (PO4) were evaluated qualitatively. Isolates showed differing solubilization zones (cm) in agar plates containing cellulose (1.8-9.5 cm), amylose (0.1-2.1 cm), tri-calcium phosphate (0.1-0.17 cm) and di-calcium phosphate (0.33-0.53 cm), to substantiate their biofertilizer potentialities. Confrontation assay with dual culture technique against seven phytopathogens (i.e. Rhizoctonia solani, Aspergillus niger, Sclerotinia sclerotiorum, S. rolfsii, Fusarium solani, F. oxysporum and Botryodiplodia theobromae) revealed promising mycoparasitic activity. Three isolates (MUSH, BIOC and V3F) showed mycelial growth inhibition in the range of 33-77%, compared to the control plate (without isolates). With respect to isolate MUSH, a significantly higher (P< 0.05) dry biomass weight (g) was obtained at pH 7 (0.66 ± 0.05) and pH 6 (0.55 ± 0.05), than at pH 3, pH 4 and pH 5. Similarly, higher biomass significance (P< 0.001) was obtained in yeast mannitol broth (2.58 ± 0.11 g), compared to potato dextrose broth (PDB) and nutrient broth (NB). The production of spores by isolate MUSH was tested on four locally available solid substrates (i.e. corn stalk, rice husk, jackfruit molasses and sugarcane bagasse) through solid state fermentation (SSF). Production of conidia (cfu/g) was higher in corn stalk (72.6 ×108 ), followed by rice husk (68.4×108 ), jackfruit molasses (18.6×108 ) and sugarcane bagasse (12.4×108 ). High counts of conidia production on these substrates render MUSH isolate efficient to be used as a BCA by the farmers, to enhance their crop productivity.